DNA Methylation Profiling Revealed Promoter Hypermethylation-induced Silencing of p16, DDAH2 and DUSP1 in Primary Oral Squamous Cell Carcinoma - Khor, Goot Heah; Froemming, Gabriele Ruth Anisah; Zain, R.B.; Abraham, Mannil Thomas; Omar, Effat; Tan, Su Keng; Tan, Aik Choon; Chong, Vincent Vui King; Thong, Kwai Lin (Ivyspring International Publisher, 2013)
BACKGROUND: Hypermethylation in promoter regions of genes might lead to altered gene functions and result in malignant cellular transformation. Thus, biomarker identification for hypermethylated genes would be very useful for early diagnosis, prognosis, and therapeutic treatment of oral squamous cell carcinoma (OSCC). The objectives of this study were to screen and validate differentially hypermethylated genes in OSCC and correlate the hypermethylation-induced genes with demographic, clinocopathological characteristics and survival rate of OSCC.